Government decentralization program in Indonesia - Anwar Nasution (Asian Development Bank Institute (ADBI), 2016)
Without much preparation, Indonesia, in 2000, at a stroke replaced the previous system of centralized government and development planning with a wide range of decentralization programs. The reforms gave greater authority, political power, and financial resources directly to regencies and municipalities, bypassing the provinces. The powers transferred include those of executing a wide range of responsibilities in the areas of health, primary and middle-level education, public works, environment, communication, transport, agriculture, manufacturing, and other economic sectors. At the same time, the government replaced the antiquated cash-based, single-entry system of public finance with a modern double-entry accounting system that uses a single treasury account; is performance based; and has transparent management of the public treasury, tight expenditure and financial controls with performance indicators, computerized reporting, and a tightly scheduled auditing system. On the positive side, unlike in many developing and transition countries, the decentralization program in Indonesia has not caused major political or economic problems. However, the decentralization program was ill prepared and not carried out in a logical order for two reasons. First, the capacity of subnational governments to produce public and private goods, increase productivity and employment, and promote economic growth in their jurisdictions, was not increased. Because of the long tradition of centralization, local government never built the capacity to carry out economic planning and undertake initiatives to promote local economic growth. Before the reform, the local governments had mainly functioned as implementing agencies of national policies and programs. Second, the number of good financial managers, as required by the new laws of public treasury and auditing, was also limited and needed to be trained. The rising revenues of local governments do not follow their increasing government functions to promote economic development that could potentially cause fiscal imbalances.
Keywords: H70; H72; H74; H77; 330; Local government; decentralization; Indonesia; government finance; fiscal reform; debt financing; state-owned enterprises; public sector